Environmental Ethics and the Need for Theory - Attfield, Robin (Studia Ecologiae et Bioethicae, 2023)
Environmental ethics calls into question whether moral obligations invariably arise within relationships and communities, and whether wrong can only be done if some identifiable party is harmed. The aim of this paper is to appraise these assumptions, to argue for negative answers, and to draw appropriate conclusions about the scope of moral standing (or moral considerability). Its findings include the conclusions that our moral obligations (or responsibilities) extend to people and non-human creatures of the foreseeable future, as far as the impacts of present actions and policies can themselves be foreseen, that, that moral standing attaches to the possible people and other living creatures of the future, and (with Derek Parfit) that ethics is to some degree impersonal, being concerned with future quality of life for whoever lives in future centuries, whether they are currently identifiable or not. This in turn requires sustainable forms of social practice and of the human population. Another conclusion is that these findings are compatible with the approach of stewardship which the author has defended elsewhere, since stewardship need neither be anthropocentric nor managerial, and precludes current and future human agents treating the natural world as we please.